Fintech lending fraud prevention strategy: A case study - Bachrudin K Una; Hendi Yogi Prabowo (Journal of Contemporary Accounting, 2022)
This study aims to determine the strategy of the Financial Services Authority (OJK) to prevent people from being trapped in fintech lending fraud. This qualitative research used case study method by employing semi-structured in-depth interview as the technique to collect data from five respondents. The research data were processed with the help of Computer Assisted Qualitative Data Analysis Software (CAQDAS), namely the NVivo 11 software application. The results show that there are three main strategies used by OJK Special Region of Yogyakarta, Indonesia to prevent the public from being scammed by fintech lending: First, massive implementation of financial literacy education in a comprehensive manner to improve public financial literacy; second, use of the Consumer Protection Portal Application (APPK) as a digital complaint service for the public and consumers to report the Financial Services Business Actors (PUJK) who are suspected of committing fintech lending fraud; third, maximizing the role of Regional Investment Alert Task Force (SWID) in publishing a list of legal and illegal financial services, including fintech lending.